Ethnography in the raw life in a Luzon village - Moeran, Brian 1944- (New York Berghahn Books, 2022)
"Ethnography in the Raw describes the author's encounters with the Philippine family into which he has married, his wife's friends and acquaintances, and their lives in a remote rural village in the rice basin of Luzon, about 130 miles northeast of Manila. The book links detailed descriptions of his Philippine family with cultural practices such as circumcision, marriage and cockfights combined with theoretical musings on the concepts of sacrifice, social exchange, patron-client relations, food, and religious symbolism. It is both anthropological fieldwork 'in the raw,' and an incisive analysis of contemporary Philippine society and culture"--
Beginnings -- People -- The Barangay -- Buying a Car -- Kinship and Names -- Tying the Knot -- Family -- For Richer, For Poorer -- Chaos and Laughter -- Language Use -- New Year's Eve -- Mobile Phones and Social Media -- Irrigation -- Rice and Classification -- Going for a Walk  -- A Pillow Tree -- Actually -- Spirits -- Birthday Parties -- No Money, No Hangover -- Wiping and Weeping -- Circumcision -- Blackness -- Japan -- The Author of Life -- Oh, George! -- OFWs -- Of Cocks and Men -- Religious Side Bets -- The Foreigner at Large -- She Love You, She Crazy -- Valentine's Day -- Crispin, Caesar and Cecilio - Drugs -- Cementeries -- Security Guards -- Elections -- Beliefs -- A Shotgun Wedding - Feria.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Filipinos -- Social conditions -- 21st century; Filipinos -- Social life and customs -- 21st century; Luzon (Philippines) -- Rural conditions; Philippines -- Social conditions -- 21st century; Philippines -- Social life and customs -- 21st century